2020
DOI: 10.1111/ner.13060
|View full text |Cite
|
Sign up to set email alerts
|

Poststimulation Block of Pudendal Nerve Conduction by High-Frequency (kHz) Biphasic Stimulation in Cats

Abstract: Objective To determine the relationship between various parameters of high‐frequency biphasic stimulation (HFBS) and the recovery period of post‐HFBS block of the pudendal nerve in cats. Materials and Methods A tripolar cuff electrode was implanted on the pudendal nerve to deliver HFBS in ten cats. Two hook electrodes were placed central or distal to the cuff electrode to stimulate the pudendal nerve and induce contractions of external urethral sphincter (EUS). A catheter was inserted toward the distal urethra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
4
13
1
Order By: Relevance
“…It is never possible to exclude β errors, though our use of a high SNR experimental system, with multiple slices and numerous repetitions per condition per slice, as well as within slice positive DC controls, together suggest such undetected effects would be variable or small in any case. Alternative mechanisms of electric fields such as ion concentration changes ( Bikson et al, 2001 ; Shapiro et al, 2020 ; Wang et al, 2020 ), fiber block ( Zhang et al, 2006 ; Zhao et al, 2014 ; Patel and Butera, 2015 ; Shapiro et al, 2020 ) and transverse axonal polarization ( Wang et al, 2018 ) are suggested for kHz stimulation at very high intensities. However these very high intensities are not expected in existing clinical applications, such as SCS, with targeted tissue some mm away from the electrode ( Lempka et al, 2015 ; Idlett et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is never possible to exclude β errors, though our use of a high SNR experimental system, with multiple slices and numerous repetitions per condition per slice, as well as within slice positive DC controls, together suggest such undetected effects would be variable or small in any case. Alternative mechanisms of electric fields such as ion concentration changes ( Bikson et al, 2001 ; Shapiro et al, 2020 ; Wang et al, 2020 ), fiber block ( Zhang et al, 2006 ; Zhao et al, 2014 ; Patel and Butera, 2015 ; Shapiro et al, 2020 ) and transverse axonal polarization ( Wang et al, 2018 ) are suggested for kHz stimulation at very high intensities. However these very high intensities are not expected in existing clinical applications, such as SCS, with targeted tissue some mm away from the electrode ( Lempka et al, 2015 ; Idlett et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We paused for > 2 s between amplitudes and > 5 s between each waveform and frequency pair. In addition to expediting the experiment, the short duration signals and low initial amplitudes also reduced the possibility of confounding carryover effects 18,39,40 , which were not observed in this study. In nerves 1-3, we terminated each binary search after identifying the minimum amplitude that blocked nerve conduction regardless of polarity, taking the block threshold only of the polarity that blocked at a lower threshold.…”
Section: Nerve Block Waveformsmentioning
confidence: 95%
“…This post‐HFBS block can reverse with time as the axonal membrane ion pump gradually restores the normal intra‐ and extra‐cellular ion concentrations. This theory can explain the post‐HFBS block shown in recent animal studies (7,8). However, based on this hypothesis, it is not necessary to use frequencies ≥5 kHz to produce the post‐HFBS block.…”
Section: Introductionmentioning
confidence: 64%
“…This eliminates the delay between the opening of sodium and potassium channels when a propagating action potential arrives at the site of HFBS, thereby preventing the generation of the action potential and causing a block of nerve conduction (9,10). However, this mechanism cannot explain the discovery in recent animal studies (7,8) that nerve block persists even after the end of HFBS because the potassium channels close quickly after terminating HFBS (10). However, our computer simulation studies (9,10) also revealed that when axonal ion channels remain open during HFBS each electrical pulse during stimulation generates large inward sodium and outward potassium currents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation